Pulsatile Flow of Two-Fluid Nonlinear Models for Blood Flow through Catheterized Arteries: A Comparative Study. (29th March 2010) - Sankar, D. S.; Lee, Usik
Abstract : The pulsatile flow of blood through catheterized arteries is analyzed by treating the blood as a two-fluid model with the suspension of all the erythrocytes in the core region as a non-Newtonian fluid and the plasma in the peripheral layer as a Newtonian fluid. The non-Newtonian fluid in the core region of the artery is represented by (i) Casson fluid and (ii) Herschel-Bulkley fluid. The expressions for the flow quantities obtained by Sankar (2008) for the two-fluid Casson model and Sankar and Lee (2008) for the two-fluid Herschel-Bulkley model are used to get the data for comparison. It is noted that the plug-flow velocity, velocity distribution, and flow rate of the two-fluid H-B model are considerably higher than those of the two-fluid Casson model for a given set of values of the parameters. Further, it is found that the wall shear stress and longitudinal impedance are significantly lower for the two-fluid H-B model than those of the two-fluid Casson model.